Elastic constants of biological filamentous colloids: estimation and implications on nematic and cholesteric tactoid morphologies. Issue 8 (14th January 2021) - Bagnani, Massimo; Azzari, Paride; De Michele, Cristiano; Arcari, Mario; Mezzenga, Raffaele
Abstract : Biological liquid crystals, such as cellulose and amyloid fibrils, show a physical behaviour difficult to predict and characterize. Here we present four different techniques to estimate the elastic constant K 1, K 2 and K 3 for three different biological filamentous colloids. Abstract : Biological liquid crystals, originating from the self-assembly of biological filamentous colloids, such as cellulose and amyloid fibrils, show a complex lyotropic behaviour that is extremely difficult to predict and characterize. Here we analyse the liquid crystalline phases of amyloid fibrils, and sulfated and carboxylated cellulose nanocrystals and measure their Frank-Oseen elastic constants K 1, K 2 and K 3 by four different approaches. The first two approaches are based on the benchmark of the predictions of: (i) a scaling form and (ii) a variational form of the Frank-Oseen energy functional with the experimental critical volumes at order–order liquid crystalline transitions of the tactoids. The third and the fourth methods imply: (iii) the direct scaling equations of elastic constants and (iv) a molecular theory predicting the elastic constants from the experimentally accessible contour length distributions of the filamentous colloids. These three biological systems exhibit diverse liquid crystalline behaviour, governed by the distinct elastic constants characterizing each colloid. Differences and similarities among the three systems are highlighted and interpreted based on the present analysis, providing a general framework to study dispersed liquid crystalline systems.